Trumpet Playing in Worship Ceremony At Higher Than Ever Church As A Christian Character Education Media (Universitas Negeri Semarang, 2021)
Trumpet is an ancient instrument from a sheep's horn found in the Bible. The worship ceremony at the Higher Than Ever Church incorporates the Trumpet instrument with modern musical instruments. This study aims to explain the value of Christian character education in the Trumpet game. The research method used wasqualitative, and the research approach was the art education approach. The data were obtained through observation, interviews, and document studies. Then data was validated using the triangulation of sources and data analysis contextualization of the synthesis model. The study results show the value of art education in the Trumpet playing in worship ceremonies at the Higher Than Ever Church, namely having characteristics of spiritual, respect, creativity, and solidarity. These four values of Christian character are implied through the Trumpet instrument, which the congregation can appliy in their social life. The conclusion from the results of this study is that the Trumpet playing has implications for Christian character values and can be applied in social life.